Effects of enhancing cetane number of ethanol fumigation on diesel engine performance and emissions - Babiker, M.E. (Asian Research Publishing Network, 2016)
This study investigated the impact of fumigating different percentages of anhydrous ethanol (E) and cetane number enhancer (CNE) on the combustion, performance as well as exhaust pollutants of DI diesel engine. The addition of this mixture (ECNE) exhibited higher premixed combustion peaks, faster combustion process, and higher coefficient of variation of indicated mean effective pressure (IMEP) and reduced maximum in-cylinder temperature, in comparison with neat diesel (D). The total combustion duration as well as the ignition delay prolonged when ECNE fumigated compared to that of diesel fuel only. The combustion characteristics of ECNE ratios at high load could be recovered to diesel fuel by introducing CN enhancer, but a large difference occurs at lower load. Neither Ethanol only nor ECNE presented better thermal efficiency (BTE) and brake specific fuel consumption (BSFC) than the baseline diesel fuel. Engine performance with ECNE fumigation is highly susceptible to operating conditions; therefore, it is necessary to optimize the specific thermal conditions for implementing a fumigation approach. ECNE increased total hydrocarbons (THC) and carbon monoxide (CO), reduced particulate matter (PM) and nitrogen oxides (NOx) in comparison with pure diesel fuel. However, the amount of this reduction was markedly affected by engine operating mode. The DECNE (85 diesel+10 ethanol+ 5Cetane enhancer) showed the best trade-off between the engine performance, combustion and emissions characteristics (PM vs NOx + THC) among the ECNE ratios. Â© 2006-2016 Asian Research Publishing Network (ARPN).